2014
DOI: 10.1177/1468087414552831
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cylinder pressure–based engine noise metrics to measured microphone data

Abstract: Peak pressure rise rate, ringing intensity, and combustion noise analysis are typically cited measures of the noise generated by combustion in an internal combustion engine. In this publication, peak pressure rise rate, ringing intensity, and the combustion noise calculation results are compared to microphone data over a wide range of engine operating conditions for one gasoline and one diesel engine. Multiple methods for calculation of peak pressure rise rate are explored, including the use of different time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…35 Shahlari et al reported that for three methods of calculating the correlation between peak pressure raise rate (PPRR) and ringing intensity (RI), there is no correlation between PPRR (all three methods) and noise, while Combustion Noise algorithm results have the best correlation ( R 2 = 0.8) with microphone noise measurement. 36 Comparing these reports with our findings, we concluded that the wavelet coherence estimates between CP and SP signals is a better way of understanding the combustion-induced noise. As Bhat et al reported that with advancing injection timing the cylinder pressure will rise, consequently we expect to measure high radiated noise.…”
Section: Resultssupporting
confidence: 83%
“…35 Shahlari et al reported that for three methods of calculating the correlation between peak pressure raise rate (PPRR) and ringing intensity (RI), there is no correlation between PPRR (all three methods) and noise, while Combustion Noise algorithm results have the best correlation ( R 2 = 0.8) with microphone noise measurement. 36 Comparing these reports with our findings, we concluded that the wavelet coherence estimates between CP and SP signals is a better way of understanding the combustion-induced noise. As Bhat et al reported that with advancing injection timing the cylinder pressure will rise, consequently we expect to measure high radiated noise.…”
Section: Resultssupporting
confidence: 83%
“…This parameter is of interest because it has been shown to be the primary driver in combustion-generated noise in engines. 86,87 In addition, the combustion noise level (CNL) is shown, which was calculated using the algorithm put forward by Shahlari et al 88 Considering these are closed-cycle simulation results, an algorithm also put forward by Shahlari et al 89 was used to calculate the full four-stroke cycle noise from closed-cycle simulation results. As shown in Table 3, CDC operation yields the lowest combustion noise, which is expected due to the mixing limited nature of the majority of the combustion process, which yields a more sedate energy release than volumetric autoignition.…”
Section: Simulated Results Of the Baseline Operating Conditionmentioning
confidence: 99%
“…Different metrics exist to quantify combustion noise, from the HCCI-suited ringing intensity (RI; MW/m 2 ) indicating the power flux delivered by the pressure waves, 29 to the Noise (dB) indicating the perceived noise outside of the engine (more indicated for conventional engine modes). 30 Given that the RI metric has been specifically developed for HCCI engines and is still being used today (see for example), 31,32 this metric uncertainty will be developed here-under. However, the uncertainty related to any other metric can be obtained following the general methodology developed in this article.…”
Section: Results: Uncertainties On the Physical Quantities Requiring mentioning
confidence: 99%